Religion, media, and social change - Granholm, Kennet; Moberg, Marcus; Sjo, Sofia (Routledge research in religion, media, and culture, 2015)
pt. 1. Theorising media and religion in the public sphere -- pt. 2. Media, popular culture and contemporary religious sensibilities and communities -- pt. 3. Impacts and outcomes of contemporary encounters between religion, media and popular culture.